Effects of whey peptide extract on the growth of probiotics and gut microbiota - Yu, Ya-Ju (2017)
Whey peptide extract with molecular weight below 1 kDa was investigated in microplate assay, and viable cells, as well as metabolic activity were determined to evaluate augmented growth of probiotic bacteria (Lactobacillus acidophilus and Bifidobacterium animalis). Results illustrated that whey peptide extract 1% (w/v) has the capacity to stimulate the proliferation of both probiotic bacteria tested, further supported by the faster generation of metabolic products. The effect of whey peptide extract on the modulation of gut microbiota was also examined inWistar rats fed either with a standard or a high-fat diet, assessed via 16S ribosomal RNA expression of gut microbiota by quantitative PCR. Relative abundance of Lactobacillus spp., Bifidobacterium spp. and Bacteroidetes was significantly increased by whey peptide extract in rats fed with a standard diet. These results highlight an additional unexploited positive effect of whey peptide extract on gut microbiota modulation.